Echoes of mercy [large type] : a novel - Sawyer, Kim Vogel (Center Point Large Print, 2014)
"Bringing to life the interworkings of a 1906 chocolate factory and one young crusader's passionate vision to see child workers free of factory work, this historical Christian Romance has a lot of heart and soul"--